The Role of Fibroblast Growth Factor 21 in Diabetic Cardiovascular Complications and Related Epigenetic Mechanisms - Xiao, Mengjie; Tang, Yufeng; Wang, Shudong; Wang, Jie; Wang, Jie; Guo, Yuanfang; Zhang, Jingjing; Gu, Junlian (Frontiers in Endocrinology, 2021)
Fibroblast growth factor 21 (FGF21), is an emerging metabolic regulator mediates multiple beneficial effects in the treatment of metabolic disorders and related complications. Recent studies showed that FGF21 acts as an important inhibitor in the onset and progression of cardiovascular complications of diabetes mellitus (DM). Furthermore, evidences discussed so far demonstrate that epigenetic modifications exert a crucial role in the initiation and development of DM-related cardiovascular complications. Thus, epigenetic modifications may involve in the function of FGF21 on DM-induced cardiovascular complications. Therefore, this review mainly interprets and delineates the recent advances of role of FGF21 in DM cardiovascular complications. Then, the possible changes of epigenetics related to the role of FGF21 on DM-induced cardiovascular complications are discussed. Thus, this article not only implies deeper understanding of the pathological mechanism of DM-related cardiovascular complications, but also provides the possible novel therapeutic strategy for DM-induced cardiovascular complications by targeting FGF21 and related epigenetic mechanism.